Circuits and Networks: Analysis and Synthesis - A.Sudhakar (Mc Graw Hill, 2008)
Part of the McGraw-Hill Core Concepts in Electrical Engineering Series, Circuits and Networks: Analysis and Synthesis is designed as a textbook for an introductory circuits course at the intermediate undergraduate level. The book may also be appealing to a non-major survey course in electrical engineering course as well.